GREEN LIFESTYLE WARGA KOTA SOLO - Irmawati, Irmawati; Waskito, Jati (Benefit, 2012)
Green Lifestyle is focused to our care for this beloved earth. A lifestyle that really makethis earth as a âpartnerâ in everyday life, not only as an âobjectâ exploitation to make ends meet.Goals to be achieved through this study are as follows: 1. Make the description of eco-friendlylifestyle in Solo City residents 2. Analyze the relationship with the eco-friendly lifestyledemographic characteristics of residents of Solo Data collection in this study is survey methodwith questionnaire instruments. To test the hypothesis that distinguishes environmentally friendlylifestyle perceptions of respondents based on their demographic characteristics, this study usesone-way ANOVA. Based on the results of data analysis can also be concluded that people withhigher education, older adult, married, and female sex have a lifestyle that is more environmentallyfriendly than less educated people, young, unmarried, and male sex.